Capacidade científica e tecnológica dos laboratórios de saúde pública de referência no Brasil - Nery Cunha Vital (2005)
The present research was carried out in order to raise up the conditions of Brazilian public health laboratories which are involved in scientific researches, by outlining the skill of the researches of the reference laboratories that are responsible for the diseases dengue, yellow fever and spot fever. The dara were collected using a self-applicable questionnaire and an attitude scale, type Likert, with affirmatives which made it possible to get to researches impression about a desirable and actual relationship about twenty-eight concepts of the following subjects: human resources, physical and operating substructure, scientific project management and scientific production setting. Each subject concept was measured using the approval and disapproval average of the each situation (actual and desirable), that was set in graphics. The contribuition of each concept relating to each of the subjects was analyzed by intenal consistency of Cronbach's alpha. Different concepts of each subject were disapproved by the researches, considering the actual situation, specially those concerning to human resources and physical and operating substructure, ocassion when high levels of expectative related to a desirable situation were identified